2018
DOI: 10.1039/c8ja00033f
|View full text |Cite
|
Sign up to set email alerts
|

An improved method of Cr purification for high precision measurement of Cr isotopes by double spike MC-ICP-MS

Abstract: A flexible, easy and highly efficient Cr purification method was developed for high-precision measurement of Cr isotopes by double-spike MC-ICP-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 59 publications
7
42
1
Order By: Relevance
“…In this study, two basalt reference materials from the USGS, BHVO‐1 (−0.120 ± 0.029‰, 2 s ) and BHVO‐2 (−0.129 ± 0.032‰, 2 s ), gave slightly lower δ 53/52 Cr NIST SRM 979 values than that of peridotite reference material JP‐1 from JSG (−0.088 ± 0.034‰; 2 s ) with the mean results over a period of two years. The data obtained in this study for these basalt and peridotite reference materials are consistent with the δ 53/52 Cr NIST SRM 979 values reported by previous studies within the precision quoted (Schoenberg et al , , Wang et al , Li et al , , Gueguen et al , Bonnand et al , b, Wu et al , Xia et al , Zhu et al ) (Figure b).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, two basalt reference materials from the USGS, BHVO‐1 (−0.120 ± 0.029‰, 2 s ) and BHVO‐2 (−0.129 ± 0.032‰, 2 s ), gave slightly lower δ 53/52 Cr NIST SRM 979 values than that of peridotite reference material JP‐1 from JSG (−0.088 ± 0.034‰; 2 s ) with the mean results over a period of two years. The data obtained in this study for these basalt and peridotite reference materials are consistent with the δ 53/52 Cr NIST SRM 979 values reported by previous studies within the precision quoted (Schoenberg et al , , Wang et al , Li et al , , Gueguen et al , Bonnand et al , b, Wu et al , Xia et al , Zhu et al ) (Figure b).…”
Section: Resultssupporting
confidence: 92%
“…Comparison of geological reference material data analysed in this study (red symbols) with literature values (black symbols) (Schoenberg et al , , Gueguen et al . , Wang et al , Li et al , , Bonnand et al , b, Xia et al , Wu et al , Zhu et al ). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Ellis et al added a 50 Cr‐ 54 Cr double spike to the sample to correct for mass‐dependent fractionation during both the TIMS measurement and the purification process; these authors obtained an external precision of ±0.2‰ on rock and groundwater samples. In the last decade, stable Cr isotopic measurements were performed by combining the double‐spike technique and multi‐collector mass spectrometry, with long‐term reproducibilities (2SD) of around 0.05‰ to 0.06‰ being reported. In 2014, Schiller et al reported a sample‐standard bracketing (SSB) method for Cr isotopic measurements.…”
Section: Introductionmentioning
confidence: 99%